Knowledge and attitude of pregnant women on congenital abnormalities - Jayaweera, L.S.E (My University, 2004)
Main objectives of the study were to determine the awareness of mothers on factors responsible for giving rise to CAs . (Chromosomal, Genetic food, Chemical etc.). Prevalence of different types of CAs in the population, Tendency to repaper the CAs in successive pregnancies in some mothers, Availability of investigation in order to detect CAs in fetal stage, and attitudes towards the congenital abnormal baby fetus were also assessed in the study. Less than 45 of the population knew approximately the incidence of abnormalities. A proportion of mothers were aware about , causative factors of CAs, at least to some extent. But majority of mothers were poor in other assessment ( 48.9) had no fear on their present pregnancy and 22.3 of the population recommended induce abortions for antenatal detached CA fetus 85.1 of mothers thought that it is better to have medical advice during future pregnancies of mothers who have had children with CAs 62.2 of the study population of mothers attitude were that a mother should bring up a child with CAs (what ever the severity is) with the help of medical treatment.